Rituximab-IgG2 is a phagocytic enhancer in antibody-based immunotherapy of B-cell lymphoma by altering CD47 expression - Nguyen, Oanh T. P.; Lara, Sandra; Ferro, Giovanni; Peipp, Matthias; Kleinau, Sandra (Frontiers in Immunology, 2024)
Antibody-dependent cellular phagocytosis (ADCP) by monocytes and macrophages contributes significantly to the efficacy of many therapeutic monoclonal antibodies (mAbs), including anti-CD20 rituximab (RTX) targeting CD20+ B-cell non-Hodgkin lymphomas (NHL). However, ADCP is constrained by various immune checkpoints, notably the anti-phagocytic CD47 molecule, necessitating strategies to overcome this resistance. We have previously shown that the IgG2 isotype of RTX induces CD20-mediated apoptosis in B-cell lymphoma cells and, when combined with RTX-IgG1 or RTX-IgG3 mAbs, can significantly enhance Fc receptor-mediated phagocytosis. Here, we report that the apoptotic effect of RTX-IgG2 on lymphoma cells contributes to changes in the tumor cell’s CD47 profile by reducing its overall expression and altering its surface distribution. Furthermore, when RTX-IgG2 is combined with other lymphoma-targeting mAbs, such as anti-CD59 or anti-PD-L1, it significantly enhances the ADCP of lymphoma cells compared to single mAb treatment. In summary, RTX-IgG2 acts as a potent phagocytic enhancer by promoting Fc-receptor mediated phagocytosis through apoptosis and reduction of CD47 in CD20+ malignant B-cells. RTX-IgG2 represents a valuable therapeutic component in enhancing the effectiveness of different mAbs targeting B-cell NHL.